Negotiating modernity Africa's ambivalent experience - edited by Elísio Salvado Macamo (Dakar Codesria Books, 2005)
Modernity is the unfinished business of our times. In the case of Africa, as the scholars contributing to this volume show, the continent has been through a particularly ambivalent experience of modernity. Most work has tended to emphasize, on the one hand, its alien nature in Africa and, on the other, the ways in which Africans have resisted it. While acknowledging this tension, the authors of this volume seek to show the extent to which this very tension has been constitutive of African social reality. Modernity is understood as the basic impulse behind the construction of changing African society over the past one hundred years. The issues that this volume addresses relate to the ways in which, first, Africans negotiated the terms of this modernity during the colonial period and, then, how today they are coming to terms with it in the post-colonial period. The contributors argue both that the African experience of modernity is unique and, at the same time, relevant for social theory more widely. Not only is it important to describe this experience, but also to acknowledge that such a description may provide African Studies with valuable analytical insights into African social reality. In the course of so doing, cases are presented and issues raised covering new forms of labour, changing notions and norms relating to land rights, religious conversion, internal migration, and even emigration. Indeed, one particularly significant, but often underplayed, feature that has characterised both the colonial and post-colonial periods, and which this book deals with extensively, is the variegated linkages and interactions between Africans in the diaspora and within the Continent.
Includes bibliographical references and index.
Keywords: Social conflict--Africa.